Road Construction in the Region in Conditions of Macroeconomic Instability ("Journal "U". Economy. Management. Finance.", 2023)
The article provides a comparative analysis of financing the construction of public roads of regional, intermunicipal and local significance. A vision for improving the financial provision of road construction through the introduction of agreements on the provision of other interbudgetary transfers for three budget cycles has been defined.
Keywords: region; road construction; construction and reconstruction of roads; financing of the road transport industry; road industry of the Republic of Bashkortostan